(untitled) (Annual of the Faculty of Philosophy in Skopje, 2010)
Not long ago the concepts of administration and leadership for designation of work organizations’ direction in our country have been applied. But due to an increased empowerment of organizational directors under transitional conditions, the tendency for their appointment as managers and the trend for the appointment of organizational direction as management have appeared. From psychological aspects, the concepts of administration and of management are explained that are compared with the concept of organizations’ leadership. Based on the interaction approach for relation among employees’ characteristics and organizations’ characteristics new direction strategies in order to attain positive issues in work process are proposed.